The opportunities and risks of employment under the impact of artificial intelligence - Guzueva Elina; Ksenofontov Alexander; Aun Danil (ITM Web of Conferences)
This paper studies the complex relationship between artificial intelligence and employment, exploring both opportunities and challenges presented by this rapidly evolving technology. As artificial intelligence continues to advance at an unprecedented pace, it is reshaping industries and raising significant concerns about its impact on jobs. The research investigates how artificial intelligence is capable of not only transforming existing roles but also potentially eliminating certain positions entirely. The study analyzes potential challenges posed by artificial intelligence integration in the workforce and proposes possible solutions to prepare for upcoming shifts in the job market. The importance of proactive measures to address challenges and harness opportunities in the evolving landscape of work is emphasized.